Cytokine modulation in abdominal septic shock via the crucial role of IL-6 signaling in endothelial dysfunction - Ueno, Takuya; Ikeda, Toshiaki; Okihara, Masaaki; Akashi, Isao; Yokoyama, Takayoshi; Kihara, Yu; Konno, Osamu; Nakamura, Yuki; Iwamoto, Hitoshi; Ueno, Yu; Chandraker, Anil (Frontiers in Medicine, 2023)
Background Early recovery from shock improves prognosis in septic shock patients. We determined whether cytokine modulation by Continuous Renal Replacement Therapy (CRRT) following acute care surgery resulted in stable hemodynamics in them. To investigate our hypothesis, we measured proinflammatory cytokines IL-6, IL-1ra and the coagulation cascade activator plasminogen activator inhibitor-1 (PAI-1) following CRRT with polymyxin B immobilized fiber (PMX-DHP) which has been utilized as an adjuvant treatment option for patients with severe septic shock. Methods 66 septic shock patients requiring 2 h direct hemoperfusion therapy PMX-DHP were included. 36 patients of them also received continuous hemodiafiltration (CHDF) after performing PMX-DHP. Circulatory dynamics and levels of inflammatory mediators, namely IL-6, IL-1ra, and PAI-1 were assessed before, immediately after, and 24 h initiation of PMX-DHP. Results Mean Arterial Pressure (MAP) rose intentionally by PMX-DHP just after enforcement 24 h later (p < 0.01). Levels of IL-6, IL-1ra, and PAI-1 significantly decreased after PMX-DHP (p < 0.05) and this trend was observed up to 24 h post initiation of PMX-DHP (p < 0.05). IL-6 modulation by PMX-DHP was enhanced with using CHDF and there was a significant correlation between IL-6 and MAP (p < 0.0001). In addition, levels of Il-6 and PAI-1 showed a significant correlation. Conclusion Our data showed employing CRRT as cytokine modulators could be an additional therapeutic strategy to improve septic shock outcomes via the crucial role of IL-6 signaling in endothelial dysfunction.